PERUBAHAN PSIKOFISIOLOGIS PADA IBU HAMIL TRIMESTER III: PENELITIAN DESKRIPTIF - Sari, Wenny Indah Purnama Eka; Kurniyati, Kurniyati; Yusniarita, Yusniarita; Mardalena, Ida (Politeknik Kesehatan Kementerian Kesehatan Banten, 2024)
During pregnancy, physiological changes occur due to hormonal shifts, particularly in estrogen and progesterone, leading to both physical and psychological alterations. The physical changes that occur during pregnancy often cause discomfort, both physically and psychologically. A common psychological change experienced by pregnant women is anxiety, while the physiological changes relate to bodily systems, resulting in alterations in vital signs. The purpose of this study is to describe the psychophysiological changes in pregnant women during the third trimester. The research design is descriptive. The population consists of all third-trimester pregnant women. The sample includes 120 third-trimester pregnant women at the maternity clinic, selected through simple random sampling. The research instruments include the Pregnancy Related Anxiety Questionnaire Revised (PRAQ-R2) to measure anxiety in pregnant women (psychological dimension) and an observation sheet to record blood pressure, respiration, and pulse (physiological dimensions). Data analysis describes anxiety levels, blood pressure, respiration, and pulse rates in third-trimester pregnant women. The results show that nearly all respondents were aged 20-35 years (80%), the majority were multigravida (57.5%), and most were employed (54.2%). The psychophysiological profile of third-trimester pregnant women indicates that most fall into the moderate anxiety category (63.3%), with an average systolic blood pressure of 133.5, diastolic of 85.13, average respiration rate of 22.92, and an average pulse rate of 91.55. Midwives play a crucial role in helping pregnant women adapt to these psychophysiological changes, covering both physical and psychological aspects, thereby ensuring the well-being of the mother and baby during pregnancy.